Twin studies on the association of physical activity with cognitive and cerebral outcomes. (July 2020) - Iso-Markku, Paula; Waller, Katja; Hautasaari, Pekka; Kaprio, Jaakko; Kujala, Urho M.; Tarkka, Ina M.
Highlights: The moderate-strength association between PA and cognition or reduced dementia incidence may be explained in part by familial factors. In MZ co-twin control design, PA may increase GM volume in striatal, prefrontal and hippocampal regions independent of familial factors. In MZ co-twin control design, LTPA may expedite preconcious visual processing and dampen strength of unattended deviant somatosensory stimuli. Abstract: Regular physical activity (PA) offers positive effects on the human body. However, the effects of PA on cognition and in the brain are less clear. In this paper, we narratively review the relationship of PA with cognition and dementia, first from general perspective and then through genetically informed studies on the topic. Then we move on to imaging studies on exercise and brain anatomy first by presenting an overall picture of the topic and then discussing brain imaging studies addressing PA and brain structure in twins in more detailed way. Regarding PA and cognition or dementia, genetically informed studies are uncommon, even though the relationship between PA and cognitive ageing has been extensively studied. It is challenging to find twin pairs discordant for PA and dementia. Concerning brain imaging studies, among PA discordant young adult twin pairs, the more active co-twins showed larger gray matter volumes in striatal, prefrontal, and hippocampal regions and in electrophysiological studies automatic deviance-detection processes differed in brain regions involved with sensorimotor, visual and memory functions.